ADCP current measurements (38 kHz) during Maria S. Merian cruise MSM88/1 - Colin W Devey; Robert Kopte (PANGAEA, 2020)
Upper-ocean velocities along the cruise track of Maria S. Merian cruise MSM88/1 were continuously collected by a vessel-mounted Teledyne RD Instruments 38 kHz Ocean Surveyor ADCP. The transducer was located at 6.5 m below the water line. The instrument was operated in narrowband mode with 32 m bins and a blanking distance of 16.0 m, while 50 bins were recorded using a pulse of 2.90 s. The ship extquotesingles velocity was calculated from position fixes obtained by the Global Positioning System (GPS). Heading, pitch and roll data from the ship extquotesingles gyro platforms and the navigation data were used by the data acquisition software VmDas internally to convert ADCP velocities into earth coordinates. Accuracy of the ADCP velocities mainly depends on the quality of the position fixes and the ship extquotesingles heading data. Further errors stem from a misalignment of the transducer with the ship extquotesingles centerline. The average interval was set to 60 s. Data post-processing included water track calibration of the misalignment angle (0.44° +/- 0.4694°) and scale factor (1.0008 +/- 0.0083) of the Ocean Surveyor signal.